A CO Adsorption Site Change Induced by Copper Substitution in a Ruthenium Catalyst for Enhanced CO Oxidation Activity. (27th December 2018) - Huang, Bo; Kobayashi, Hirokazu; Yamamoto, Tomokazu; Toriyama, Takaaki; Matsumura, Syo; Nishida, Yoshihide; Sato, Katsutoshi; Nagaoka, Katsutoshi; Haneda, Masaaki; Xie, Wei; Nanba, Yusuke; Koyama, Michihisa; et al.
Abstract: Ru is an important catalyst in many types of reactions. Specifically, Ru is well known as the best monometallic catalyst for oxidation of carbon monoxide (CO) and has been practically used in residential fuel cell systems. However, Ru is a minor metal, and the supply risk often causes violent fluctuations in the price of Ru. Performance‐improved and cost‐reduced solid‐solution alloy nanoparticles of the Cu‐Ru system for CO oxidation are now presented. Over the whole composition range, all of the Cu x Ru1− x nanoparticles exhibit significantly enhanced CO oxidation activities, even at 70 at % of inexpensive Cu, compared to Ru nanoparticles. Only 5 at % replacement of Ru with Cu provided much better CO oxidation activity, and the maximum activity was achieved by 20 at % replacement of Ru by Cu. The origin of the high catalytic performance was found as CO site change by Cu substitution, which was investigated using in situ Fourier transform infrared spectra and theoretical calculations. Abstract : Mit Kupfer aus dem Loch kommen : Eine gesenkte CO‐Adsorptionsenergie auf Ru‐Atomen durch Zulegieren von Cu‐Atomen ist wichtig für die höhere CO‐Oxidationsaktivität von Cux Ru1− x ‐Nanopartikeln. Als Ursache wird ein Wechsel der CO‐Adsorptionsposition experimentell und theoretisch bestätigt.